Development of Al-Qur'an-Based Physics Learning Media Applications to Improve Higher Order Thinking Skills and Spiritual Attitudes for Preservice Physics Teacher - Lailatul Nuraini; Firdha Kusuma Ayu Anggraeni; Alex Harijanto; Sri Handono Budi Prastowo; Subiki Subiki; Bambang Supriadi; Maryani Maryani; Sutarto Sutarto; Rayendra Wahyu (Universitas Ahmad Dahlan, 2022)
This study aims to develop an Android-based Al-Qur'an integrated physics learning media to improve preservice physics teachers' higher-order thinking skills and spiritual attitudes. The development of learning media uses the ADDIE model. Media and material experts assessed the feasibility of learning media through a validation questionnaire. The trial was carried out on 40 preservice physics teacher students. The validation results were analyzed using a descriptive technique. The analysis results show that the learning media developed is suitable for improving Higher Order Thinking Skills and the Spiritual Attitude of Preservice Physics Teachers. So, the Android-based physics learning media integrated with the Quran can be implemented for preservice physics teachers.